Collagen and Elastic Fiber Content Correlation Analysis between Horizontal and Vertical Orientations of Skin Samples of Human Body. (14th September 2015) - Kumar, Naveen; Kumar, Pramod; Nayak Badagabettu, Satheesha; Kudva, Ranjini; Surendran, Sudarshan; Adiga, Murali
Abstract : Background . Unequal distribution of dermal collagen and elastic fibers in different orientations of skin is reported to be one of the multifocal causes of scar related complications. Present study is to understand the correlation pattern between collagen in horizontal (C H ) and in vertical (C V ) directions as well as that of elastic in horizontal (E H ) and vertical (E V ) directions. Materials and Method . A total of 320 skin samples were collected in two orientations from suprascapular, anterior chest, lateral chest, anterior abdominal wall, and inguinal regions of 32 human cadavers. Spearman correlation coefficient ( r ) was calculated between the variables (C H, C V, E H, andE V ). Results . Significant positive correlation betweenC H andC V, and betweenE H andE V observed in all 5 areas tested. A negative correlation betweenC V andE V at suprascapular, lateral chest, and inguinal regions and negative correlation betweenC H andE H at anterior chest and anterior abdominal wall have been identified. Conclusion . Knowledge of asymmetric content of dermal collagen and elastic fibers together with the varied strength and degree of association in the given area provides guidelines to the dermatologists and aesthetic surgeons in placing elective incisions in the direction maximally utilizing the anatomical facts for aesthetically pleasing result.